Greenhouse gases concentrations influence on vertical distribution of nematode communities in the Ba Lai river, Vietnam - Thai Thanh, Tran; My Yen, Nguyen Thi; Ngoc Hoai, Pham; Nguyen Lu Nguyet , Hang; Nguyen Van, Dong; Ngo Xuan, Quang (Academia Journal of Biology, 2023)
Vertical distribution of free–living nematodes from the tropical region are still poorly documented, especially in Vietnam. Field sampling was conducted at the Ba Lai river, a tributary of the Mekong river, to insight into the regularity of the vertical pattern of nematode assemblages. Furthermore, some sediment environmental characteristics such as greenhouse gases were also detected in order to understand how to influence nematode distribution. The study found that nematode composition differed significantly between the upper and deeper layers of sediment but not among the deeper layers. Nematode density showed spatial variability across layers, with higher values in the upper layer. Nematode diversity decreased with increasing depth. Non–selective deposit feeders (1B) were dominated in the surface layers, while the predator–omnivores feeders (2B) was numerous in the deeper layers. In the dry season, both methane and hydrogen sulfur were found negatively affecting nematode diversity in sediment profile, particularly, methane effects negatively also to species richness, densities, and evenness. However, only methane has a significant correlation to the diversity, species richness, densities, and evenness of the nematode communities.